1997
DOI: 10.1161/01.str.28.1.26
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle-Associated Risk Factors for Acute Brain Infarction Among Persons of Working Age

Abstract: Recent heavy drinking of alcohol, hypertension, cardiac disease, current smoking, diabetes, and history of migraine among men, and recent heavy drinking of alcohol, current use of oral contraceptives, and current smoking among women, seem to be independent risk factors for acute brain infarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
86
1
9

Year Published

1998
1998
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(98 citation statements)
references
References 32 publications
2
86
1
9
Order By: Relevance
“…Our findings regarding the gender disparity of these vascular risk factors are in line with other studies. 6,22,23 The importance of classical vascular risk factors for strokes in the young is further substantiated by our finding of a high prevalence of silent infarcts and WMHs on MRI: silent infarcts were present in 20% of patients with a firstever ischemic stroke and in 11% of patients with first-ever TIA (and no previous stroke), and WMHs of any degree were present in almost half of all patients. Whereas silent infarcts and WMHs are quite common in the elderly general population, they are distinctly uncommon in persons <55 years: in the Framingham Offspring Study <8% of persons aged 30 to 49 years had a silent brain infarct, and other studies have reported even lower rates.…”
Section: Discussionmentioning
confidence: 68%
“…Our findings regarding the gender disparity of these vascular risk factors are in line with other studies. 6,22,23 The importance of classical vascular risk factors for strokes in the young is further substantiated by our finding of a high prevalence of silent infarcts and WMHs on MRI: silent infarcts were present in 20% of patients with a firstever ischemic stroke and in 11% of patients with first-ever TIA (and no previous stroke), and WMHs of any degree were present in almost half of all patients. Whereas silent infarcts and WMHs are quite common in the elderly general population, they are distinctly uncommon in persons <55 years: in the Framingham Offspring Study <8% of persons aged 30 to 49 years had a silent brain infarct, and other studies have reported even lower rates.…”
Section: Discussionmentioning
confidence: 68%
“…88 Thirty percent of women with cerebral infarction in a study by Hilton-Jones and Warlow 97 were found to be OC users; 15% of the patients had a history of migraine. In a study of women with first stroke, Haapaniemi et al 98 found OC use to be an independent risk factor for ischaemic brain infarction. Among 15 to 44-yearold OC users who had had a cerebral thromboembolic attack studied by Lidegaard 99 during a 5-year period in Denmark, the risk of stroke was six times greater among diabetic women who had had previous thrombotic disease, and three times greater among women with hypertension or migraine.…”
Section: Journal Of Human Hypertensionmentioning
confidence: 99%
“…Young patients differ from other patients with stroke with regards to risk factors, causes, and outcome of stroke. [20][21][22][23][24][25] Therefore, the objectives of our study were to characterize PI and PSI in young patients with first-ever stroke and to explore whether they are associated with worse 3-month outcome and longterm mortality or recurrent vascular events.…”
mentioning
confidence: 99%